Irradiation with UV‐C inhibits TNF‐α‐dependent activation of the NF‐κB pathway in a mechanism potentially mediated by reactive oxygen species. (15th December 2016) - Szoltysek, Katarzyna; Walaszczyk, Anna; Janus, Patryk; Kimmel, Marek; Widlak, Piotr
Abstract : Pathways depending on the NF‐κB transcription factor are essential components of cellular response to stress. Plethora of stimuli modulating NF‐κB includes inflammatory signals, ultraviolet radiation (UV) and reactive oxygen species (ROS), yet interference between different factors affecting NF‐κB remains relatively understudied. Here, we aim to characterize the influence of UV radiation on TNF‐α‐induced activity of the NF‐κB pathway. We document inhibition of TNF‐α‐induced activation of NF‐κB and subsequent suppression of NF‐κB‐regulated genes in cells exposed to UV‐C several hours before TNF‐α stimulation. Accumulation of ROS and subsequent activation of NRF2, p53, AP‐1 and NF‐κB‐dependent pathways, with downstream activation of antioxidant mechanisms (e.g., SOD2 and HMOX1 expression), is observed in the UV‐treated cells. Moreover, NF‐κB inhibition is not observed if generation of UV‐induced ROS is suppressed by chemical antioxidants. It is noteworthy that stimulation with TNF‐α also generates a wave of ROS, which is suppressed in cells pre‐treated by UV. We postulate that irradiation with UV‐C activates antioxidant mechanisms, which in turn affect ROS‐mediated activation of NF‐κB by TNF‐α. Considering a potential cross talk between p53 and NF‐κB, we additionally compare observed effects in p53‐proficient and p53‐deficient cells and find the UV‐mediated suppression of TNF‐α‐activated NF‐κB in both types of cells. Abstract : TNF‐α‐induced activation of NF‐κB is inhibited by the prior irradiation with UV‐C. Suppression of TNF‐α‐activated NF‐κB is mediated by UV‐induced ROS. Inhibitory effect of UV is observed in both p53‐proficient and p53‐deficient cells.